CHARACTERISTICS OF NEONATAL ADAPTATION AND CONDITION OF INFANTS BORN TO MOTHERS WHO SUFFER OR RECOVERED FROM SYPHILIS - Маисеенко, Нина Александровна; Шишкина, Елена Викторовна; Галактионова, Марина Юрьевна; Маисеенко, Дмитрий Александрович (Mother and Baby in Kuzbass, 2017)
A retrospective analysis of 134 records of infants born to mothers who suffered or recovered from syphilis infection was conducted in Krasnoyarsk maternity hospital N 1 in 2015. Neonatal adaptation period of children born to seropositive for syphilis mothers was of a complicated nature and proceeded with the development of respiratory and cerebral distress. Infants were born with signs of morphofunctional dismaturity, Banti's syndrome and lower index of body weight and length in comparison with the control group.
Keywords: newborns; syphilis; childbearing; fetal growth retardation